Towards a trickster science/fiction: complexifying boundaries with Neal Stephenson and Michel Serres. (3rd July 2017) - Ingwersen, Moritz
ABSTRACT: This article highlights an intersection between the science fiction of Neal Stephenson and the science philosophy of Michel Serres. As two of the most prolific contemporary advocates of the communication between literature and science, Serres and Stephenson employ permutations of the trickster figure as a potent lens on the epistemological transformations that occur when boundaries are crossed and static systems perturbed. Allegorizing the birth of science and rational consciousness as the intervention of a trickster, Stephenson finds in hackers and couriers the same generative force that Serres associates with the Greek god Hermes and the figure of the parasite. With particular attention to Stephenson's postcyberpunk novel Snow Crash (Stephenson, Neal. 1992. Snow Crash . London: Penguin Books) and Serres' Hermes series (1969–1980), the concept of the trickster will be explored as both a personification of the kinship between creation mythologies, information theory, anthropology, and modern physics, and as the template for a productive transdisciplinary mode of cultural inquiry.